J0S3PHK
J0S3PHK
18-03-2016
Mathematics
contestada
substitute y-x+6 x-2y=-6
Respuesta :
daniellionyang
daniellionyang
18-03-2016
I'm assuming equation 1 is y=x+6. x-2(x+6)=-6=>x-2x-12=-6=>-x=6=>x=-6. Solving for y, y=-6+6=0. (-6,0) is the answer.
Answer Link
VER TODAS LAS RESPUESTAS ( 97+ )
ACCESS MORE
Otras preguntas
Use the model below to calculate 2 3 × 3 4 2 3 × 3 4 . A rectangle is shown divided into 3 rows and 4 columns. 3 of the 4 columns are shaded blue.
Factorize k2-2kp+p2 Who can help me out
Rewrite the expression 2 ÷ 5 as a fraction with the same numbers.
Read this sentence from an article titled “The Sunken Treasure.” Before Captain Phips left London, King James made him a knight; so that, instead of the obscure
i need an answer for these questions so i can raise my grade please help please make these answers plain and simple like the example on the image
Which phrase best completes the diagram? Causes of modern economic problems in Italy Historical overuse of natural resources Worldwide economic crisis in 2008
3. Which goddess would I make this prayer to: Dear goddess. Please bring peace and happiness to my home so I feel love like the warmth of the flames from the FI
What was an effect of the 1954 Vietnam treaty? Vietnam was divided into two parts. North Vietnam became democratic. South Vietnam became communist. France ga
How of the students have Computers at home?
How many oxygen atoms are there for three molecules of glucose (3C6H1206)? 1 3 6 18